2021
DOI: 10.1111/adb.13034
|View full text |Cite
|
Sign up to set email alerts
|

Acute alcohol intoxication modulates the temporal dynamics of resting electroencephalography networks

Abstract: This study aimed to provide a currently missing link between general intoxication‐induced changes in overall brain activity and the multiple cognitive control deficits typically observed during acute alcohol intoxication. For that purpose, we analyzed the effects of acute alcohol intoxication (1.1‰) on the four archetypal electroencephalography (EEG) resting networks (i.e., microstates A–D) and their temporal dynamics (e.g., coverage and transitions from one microstate to another), as well as on self‐reported … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(3 citation statements)
references
References 76 publications
0
2
0
Order By: Relevance
“…Recently, other interesting EEG-based approaches are emerging and need further research to better characterize patients with SUDs, mainly at the individual level. This is the case of connectivity measures, 14 microstates analysis, 34 and machine learning. 35…”
Section: Discussionmentioning
confidence: 99%
“…Recently, other interesting EEG-based approaches are emerging and need further research to better characterize patients with SUDs, mainly at the individual level. This is the case of connectivity measures, 14 microstates analysis, 34 and machine learning. 35…”
Section: Discussionmentioning
confidence: 99%
“…The Amsterdam Resting-State Questionnaire (ARSQ) [ 16 , 17 ] assesses ten mind-wandering domains that participants might experience during the resting session: Discontinuity of Mind (DoM), referring to the dynamics of ongoing thoughts; Theory of Mind (ToM), referring to other-people-related thoughts; Self, referring to self-related thoughts; Planning, referring to future-directed thoughts; Sleepiness, referring to the level of drowsiness; Comfort, referring to the level of relaxation during the session; Somatic Awareness (SA), referring to the interoceptive awareness of one’s own body; Health Concern (HC), referring to general well-being; Visual Thought (Vis), referring to visual imagery during mind wandering; and Verbal Thought (VT), referring to spontaneous thoughts formulated in words. Several EEG, fMRI, and behavioral studies have reported the relationship between ARSQ domains and physiological or psychological variables in healthy [ 16 , 17 , 18 , 19 , 20 , 21 , 22 , 23 , 24 , 25 , 26 ] and clinical cohorts [ 27 , 28 ], confirming the importance of combined measures of subjective experience and biologically defined signals.…”
Section: Introductionmentioning
confidence: 85%
“…Here, we follow a neural trait approach to examine how basic neural processing at rest may help explain the sources of individual levels of aggression. The neural trait approach involves measuring stable characteristics in resting-state brain recordings and investigating whether these characteristics are associated with cognitive, biological, and behavioral processes (e.g., Schiller et al 2014 , 2020a , b , 2021 ; Leota et al 2021 ; Nash et al 2022 ; Kleinert et al 2022 ). This task-independent approach compliments existing, task-dependent analyses of neural and psychological processes (for more on the benefits of task-independence, see Berkman and Falk 2013 ).…”
Section: Introductionmentioning
confidence: 99%